Performance Analysis of Fair UAV MAC Protocol Based on Uplink NOMA in Indoor Disaster Environment - Kang, Junghwa; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2022)
Unmanned aerial vehicles (UAVs) serve as aerial base stations when cellular networks are disrupted in indoor disaster situations. Non-orthogonal multiple access technology is being used as a technology to increase throughput and spectrum efficiency. In this paper, we propose a UAV scheduling algorithm using non-orthogonal multiple access technology for efficient communication in indoor disaster environment. The proposed algorithm considers a realistic environment using a new path loss model. The proposed algorithm can guarantee better throughput and fairness through scheduling. In simulation results, we confirm that the proposed algorithm can improve throughput and fairness than conventional MAC protocol.
Keywords: Indoor Disaster Environment; Medium Access Control (MAC); Non-Orthogonal Multiple Access (NOMA); Unmanned Aerial Vehicle (UAV)